PELAKSANAAN PENDAFTARAN AKTA PEMBERIAN HAK TANGGUNGAN YANG MELEBIHI BATAS WAKTU PENDAFTARAN BERDASARKAN UNDANG-UNDANG NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN (Studi Kasus di Kantor Pertanahan Kabupaten Boyolali) - SUWANDI, SUWANDI (Dinamika Hukum, 2019)
The purpose of this study is to: 1) Review and analyse the implementation of the registration of a Deed Granting a dependent by a conveyancer exceeding the deadline for registration at the Land Office Boyolali Regency. 2) review and analyze the consequences of the ruling against Certificate Awarding a late Dependent was enrolled in Boyolali District Land Office. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interviews and observations. To analyze the data, the researchers used a qualitative descriptive methods of analysis. Based on the research results obtained conclusions that: 1) the implementation of the registration of a deed Granting a dependent by a conveyancer exceeding the deadline for registration at the Land Office Boyolali Regency implemented can still be accepted, but the Office Land tenure obligates a conveyancer Boyolali Regency too late to make the affidavits and statements late accompanied reasons of delay and file registration rights that dependents can receive and remain unprocessed because in section 114 subsection (7) Regulation of the Minister of State Agrarian/head of National Land Agency Number 3 Year 1997 regarding the implementation of the provisions of the Government Regulation Number 24 year 1997 Regarding land registry has mentioned that the